Information systems as a reference discipline: Current debate and future directions - Baskerville, Richard; Myers, M. (Routledge, 2018)
© 2018 selection and editorial matter, Robert D. Galliers and Mari-Klara Stein; individual chapters, the contributors. In our 2002 article we suggested that it might be time for the field of information systems to be considered as a reference discipline for others (Baskerville and Myers 2002). For the previous two decades the conventional wisdom among information systems (IS) researchers had been that IS is an applied discipline drawing upon other, more fundamental, reference disciplines. These reference disciplines were seen as having foundational value for IS. Before our 2002 article the only arguments concerning this topic had been about which disciplines should be regarded as reference disciplines. No one had actually questioned this conventional wisdom, that perhaps it was time for IS itself to be considered as a reference discipline for others. In our 2002 article we did not claim that IS had in fact achieved the status of a reference discipline; rather, we suggested that it was time to at least consider this question. We said that our paper was designed to be provocative and rhetorical in order to stimulate discussion about the nature and status of our field.